Role of tissue eosinophils in chronic rhinosinusitis–associated olfactory loss. Issue 10 (25th July 2017) - Hauser, Leah J.; Chandra, Rakesh K.; Li, Ping; Turner, Justin H.
Abstract : Background: Olfactory dysfunction is 1 of the hallmark symptoms of chronic rhinosinusitis (CRS). Eosinophilic inflammation has been implicated as a potential causative factor. However, prior studies have been limited by retrospective study designs, concomitant use of systemic corticosteroids, and other confounding factors. Methods: CRS and healthy non‐CRS control subjects undergoing endoscopic sinus or skull‐base surgery were prospectively enrolled and completed olfactory testing utilizing the 40‐item Smell Identification Test (SIT) immediately prior to surgery. Histopathological evaluation of tissue excised from the ethmoid bulla was performed by a pathologist in a blinded fashion. Disease severity and patient‐reported outcomes were measured via the Lund‐Mackay computed tomography (CT) grading system and 22‐item Sino‐Nasal Outcome Test (SNOT‐22), respectively. The associations between olfactory function, tissue eosinophilia, and disease severity were analyzed using Spearman rank order correlation and multiple linear regression. Results: Twenty‐seven (27) subjects with CRS without nasal polyps (CRSsNP), 32 subjects with CRS with nasal polyps (CRSwNP), and 10 healthy non‐CRS controls were enrolled. CRSwNP was associated with higher mean tissue eosinophil counts (71.6 vs 28.1 eosinophils/high‐power field [HPF], p < 0.05) and lower age/sex‐adjusted SIT scores (−17.4 vs −6.2, p < 0.001) when compared to CRSsNP. SIT scores were strongly negatively correlated with tissue eosinophil counts in CRSwNP ( r = −0.60, p = 0.0003), but not CRSsNP ( r = 0.16, p = 0.42). The correlation between olfactory function and tissue eosinophilia in CRSwNP persisted after adjusting for disease severity. Conclusion: Tissue eosinophilia is associated with olfactory loss in CRSwNP, independent of disease severity. These results suggest a possible role for eosinophils or eosinophil‐associated cytokines in CRS‐associated olfactory loss.